Predicting The Effectiveness of Online Exam Platforms With LMS to Improve Online Learning Using The Cobit 5 Method - Zulham Sitorus; Hindra Syahputra; Bambang Sugito; Ibrahim (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Distance learning today is not just about getting online content and creating interactive and collaborative learning experiences. The aim of this research is to analyze the extent to which the online test platform is effective using Cobit Method 5. The respondents in this study were 50 students in computer systems and 10 lecturers in computer systems. The research methods used are governance audits: planning, field inspection, reporting, and follow-up. With data analysis using SPSS 20. The results of the study refer to the calculation; the level of ability (performance) obtained is a figure of 4.02, which belongs to the established level, which indicates that the process has been implemented using a defined process and has the ability to achieve the desired process result (result). While the expected level of capacity obtains a number of 4.35, which is included in the predictable level, indicating that processes have been started and operated with defined limits ensures that the performance of the process helps the organization's goals and process objectives.